The Impact of Minecraft-Based Gamification on Islamic Education Learning Outcomes: Evidence from a Santichon Islamic School (SIS) Bangkok Thailand - Abdunrorma Sama alee; Busahdiar Busahdiar; Salmiati Salmiati (CV. Zamron Pressindo, 2025)
Research Objective – This study aims to evaluate the effectiveness of gamified learning media utilizing Microsoft Minecraft in enhancing student learning outcomes in Islamic education at Santichon Islamic School, Bangkok, Thailand. The research addresses the need for innovative pedagogical approaches to improve student engagement and performance in religious education, particularly among digital-native learners. Methodology – Employing a quasi-experimental quantitative design, the study involved 50 students divided equally into experimental and control groups. The experimental group received instruction through Minecraft-based gamified media, while the control group followed conventional teaching methods. A pre-test and post-test were administered, and the data were analyzed using paired and independent sample t-tests via SPSS to assess learning gains and inter-group differences. Findings – The results indicated a statistically significant improvement in the experimental group’s post-test scores compared to the control group (p < 0.01). Students in the Minecraft group demonstrated higher engagement and a mean learning gain more than double that of the control group. These findings confirm the positive impact of gamification on cognitive learning outcomes in Islamic education. Research Implications/Limitations – This study highlights the pedagogical potential of integrating gamified digital tools in Islamic curricula. However, the research was limited to one institution and short-term assessment. Broader studies across diverse settings and longer durations are needed. Originality/Value – The study contributes to the limited empirical literature on gamification in Islamic education, offering evidence-based insight into the effectiveness of Minecraft as a digital instructional tool in religious learning environments.